The Role of Bhabinkamtibmas in the Maintenance of Public Security and Order: A Case Study of the Barumun Sector Police - R Pasaribu, Djamaludin; Zarzani, T. Riza; Aspan, Henry (International Conference Epicentrum of Economic Global Framework, 2026)
Public Security and Order Maintenance (Harkamtibmas) is one of the essential prerequisites for achieving social stability, public welfare, and sustainable development. Based on Law Number 2 of 2002 concerning the Indonesian National Police, one of the primary duties of the Indonesian National Police (Polri) is to maintain public security and order. In carrying out this responsibility, Polri implements Community Policing (Polmas) as regulated under Chief of Police Regulation Number 3 of 2015 concerning Community Policing, which designates Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat (Bhabinkamtibmas) as the Community Policing officer at the village or sub-district level. Bhabinkamtibmas is responsible for conducting community development, early detection of potential security threats, mediation, problem-solving, and building partnerships with the community to create a safe, orderly, and conducive environment. This study aims to analyze the role of Bhabinkamtibmas in realizing Public Security and Order Maintenance (Harkamtibmas) in Gunung Intan Village, Barumun Selatan District, Padang Lawas Regency, to identify the obstacles encountered in carrying out its duties based on the provisions of Chief of Police Regulation Number 3 of 2015 concerning Community Policing, and to examine the efforts undertaken to overcome these obstacles. This research employs an empirical legal research method using a qualitative approach. Data were collected through interviews, observations, and documentation involving Bhabinkamtibmas officers, village officials, community leaders, and local residents. The findings reveal that Bhabinkamtibmas plays a strategic role in maintaining public security and order through community development activities, legal education, conflict mediation, problem-solving, routine community visits, and coordination with village authorities and community leaders in accordance with the duties and functions mandated by Chief of Police Regulation Number 3 of 2015 concerning Community Policing. These activities contribute to enhancing public legal awareness, preventing social conflicts, strengthening community participation, and creating a safe, orderly, and conducive social environment. However, the implementation of Bhabinkamtibmas’ duties continues to face several challenges, including limited facilities and infrastructure, low legal awareness among some members of the community, insufficient public participation, and the geographical conditions of the assigned areas. To address these challenges, Bhabinkamtibmas continues to strengthen communication, cooperation, community involvement, and preventive measures in maintaining environmental security. This study concludes that the implementation of Bhabinkamtibmas’ duties, as mandated by Law Number 2 of 2002 concerning the Indonesian National Police and Chief of Police Regulation Number 3 of 2015 concerning Community Policing, has played a significant role in realizing Public Security and Order Maintenance (Harkamtibmas) in Gunung Intan Village. The findings further indicate the need to strengthen community policing programs, enhance public legal awareness, and increase support from various stakeholders to improve the effectiveness of maintaining public security and order at the village level.